Perbandingan Pelbagai Kaedah Pengekstrakan Air Labisia pumila var. alata - Jamia Azdina Jamal; Azmira Akmal Sateri; Khairana Husain; Ibrahim Jantan; Mohd Shahidan Mohd Arshad (penerbit ukm, 2006)
The water decoction of Labisia pumila var. alata is used traditionally in childbirth, as well as for the treatment of flatulence, dysentery, dysmenorrhoea and join pains. This study was carried out to determine the best method and optimum parameters of aqueous axtraction of the leaves and roots of this species. The laboratory methos esed were maceration, ddecoction, reflux and Saxhlet, whereas the parameters studied were temperature, duration and pH of axtraction. The yields and thin layer chromatographic profiles of the freeze-dried extracts were analysed. The study showed that in general the percentage yields of the water soluble extracts were higher for the roots than the leaves, as well as the extracts obtained from heating than those obtained at room temperature. The most effective extraction parameters for L. pumila var. alata were as follows:maceration (25 C, at least 6 hr), decoction (60 C, not exceeding 10 min) and reflux (100 C, not exceeding 4 hr). Saxhlet method was found to be the least effective. The pH analysis had shown the possibility of degradation of some of the phytochemicals at extreme pH values of 1,2 and 14.